ATIP LEVELS ARE ASSOCIATED WITH LESS AMYLOID-Β BURDEN IN POSTMORTEM BRAINS OF OLDER ADULTS WITH ALZHEIMER'S DEMENTIA. (20th December 2022) - Cosarderelioglu, Caglar; Plaza-Rodriguez, Alma; Iglesias, Pablo; Talbot, C Conover; Foster, D Brian; Cole, Robert N; Walston, Jeremy; Abadir, Peter M
Abstract: Angiotensin system, aging, and Alzheimer's disease are tightly linked. Of the brain angiotensin receptors, the subtype 2 receptor (AT2R) is relatively less studied. Canonically, the AT2R functions through nitric oxide release, and its activation has been linked to vasodilatation and neurite outgrowth as well as anti-inflammation. How AT2R signals is not known, however, an AT2R-binding protein (ATIP) has been recently described. Controversies exist on the link between ATIP and AT2R functions. Here, we describe the development of the first non-antibody based ultra-sensitive and specific quantitative mass spectrometry assay for ATIP. Using a technique that permits targeted analysis of multiple peptides across multiple samples in a single mass spectrometry run, known as TOMAHAQ, we have identified specific human tryptic peptides that permit quantification of ATIP abundance. We have used this method to quantify ATIP in postmortem frontal cortex samples of older adults (n= 60) with Alzheimer's dementia (AD). We correlated levels of ATIP to brain RAS receptors, and biomarkers of AD pathogenesis including oxidative stress, inflammation, mitochondrial dysfunction as well as amyloid-β, and tau burden. Our results show that ATIP expression (ANLKNPQIMYLEQELESLK sequence of ATIP) is positively correlated with neuronal nitric oxide synthase (nNOS) (p = 0.009, r = 0.337). Furthermore, expression of ATIP is negatively correlated with amyloid-β load in several brain regions including hippocampus (p= 0.014, r= -0.317), entorhinal cortex (p= 0.010, r= -0.331), frontal cortex (p= 0.023, r= -0.294), and overall (p= 0.004, r= -0.365). These results highlight a potential protective role for ATIP in Alzheimer's disease.